2018
DOI: 10.3762/bjnano.9.77
|View full text |Cite
|
Sign up to set email alerts
|

Noble metal-modified titania with visible-light activity for the decomposition of microorganisms

Abstract: Commercial titania photocatalysts were modified with silver and gold by photodeposition, and characterized by diffuse reflectance spectroscopy (DRS), X-ray powder diffraction (XRD), X-ray photoelectron spectroscopy (XPS) and scanning transmission electron microscopy (STEM). It was found that silver co-existed in zero valent (core) and oxidized (shell) forms, whereas gold was mainly zero valent. The obtained noble metal-modified samples were examined with regard to antibacterial (Escherichia coli (E. coli)) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 81 publications
0
41
0
Order By: Relevance
“…Based on their structural morphology, it has been hypothesized that the destruction caused by titania photocatalysis would not be effective. However, from our previous studies, it has been known that although titania could not cause the complete fungal growth inhibition, it could cause the reduction of spores' number and mycotoxin generation [33,35,38]. The highest sensitivity of fungi to titania, activated under irradiation, was observed for young cells just after germination (on day 1).…”
Section: Discussionmentioning
confidence: 92%
“…Based on their structural morphology, it has been hypothesized that the destruction caused by titania photocatalysis would not be effective. However, from our previous studies, it has been known that although titania could not cause the complete fungal growth inhibition, it could cause the reduction of spores' number and mycotoxin generation [33,35,38]. The highest sensitivity of fungi to titania, activated under irradiation, was observed for young cells just after germination (on day 1).…”
Section: Discussionmentioning
confidence: 92%
“…Previous study reported that the generated ROS initially attack the cell wall membrane and cause detachment of cell wall (Kiwi andNadtochenko, 2005, Lemire et al, 2013). Longer irradiation time is needed to induce disruption of cytoplasmic membrane followed by DNA and protein damage that are leading to cell death (Carre et al, 2014, Daly et al, 2007, Endo et al, 2018. The plot in Figure 5-6 show the relationship between the energy of light (hv) on the abscissa and the quantity of (F(R)hv) 1/2 on the ordinate.…”
Section: Factors Governing Photocatalytic Performancementioning
confidence: 99%
“…This technique substitutes the metal (titanium) or the non-metal (oxygen) component in order to alter the optical properties of TiO 2 nanomaterial. The study byEndo et al (2018) show that doped the commercial Titania samples with metal such as silver or gold result in excellent visible-light driven photodecomposition of microorganisms. An alternative technique…”
mentioning
confidence: 98%
“…Antibacterial activity was evaluated using Escherichia coli K12 (ATCC29425, Manassas, VA, USA) as a model of bacteria. The procedure was described elsewhere [31]. In brief, 10 mg of sample was suspended in 7 mL of bacterial suspension (ca.…”
Section: Activity Testsmentioning
confidence: 99%